2001
DOI: 10.1021/ja003052x
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside−Nucleic Acid Interactions:  Remarkable Stabilization of DNA and RNA Triple Helices by Neomycin

Abstract: The stabilization of poly(dA).2poly(dT) triplex, a 22-base DNA triplex, and poly(rA).2poly(rU) triple helix by neomycin is reported. The melting temperatures, the association and dissociation kinetic parameters, and activation energies (E(on) and E(off)) for the poly(dA).2poly(dT) triplex in the presence of aminoglycosides and other triplex binding ligands were determined by UV thermal analysis. Our results indicate that: (i) neomycin stabilizes DNA triple helices, and the double helical structures composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 106 publications
4
139
0
Order By: Relevance
“…There is extensive evidence describing the ability of aminoglycosides (e.g. neomycin) to bind both duplex and triplex forms of DNA, in addition to quadruplex structures, DNA:RNA hybrids, and to some extent, single-stranded nucleic acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive evidence describing the ability of aminoglycosides (e.g. neomycin) to bind both duplex and triplex forms of DNA, in addition to quadruplex structures, DNA:RNA hybrids, and to some extent, single-stranded nucleic acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A rationale has been provided for the differential effects of 2,6-, 2,7-and 1,4-disubstituted anthraquinone derivatives on triplex stabilization [127,128]. Molecular modelling has also suggested that neomycin displays a good charge and shape complementarity with the Watson-Hoogsteen groove of triplexes [124,129].…”
Section: Structural Featuresmentioning
confidence: 99%
“…It has been demonstrated that several different types of small molecules act as inhibitors of various biological, RNA-catalyzed, key processes (Sucheck & Wong, 2000;Arya et al, 2001;Bryan et al, 2004;Bakkour et al, 2007), These inhibitors are useful for investigating the pre-mRNA splicing mechanism (Hertweck et. al, 2003;Kaida et.…”
Section: Ribozyme Inhibitorsmentioning
confidence: 99%
“…The probable mode of action by methyl mercury would be through its positive ionic charge since it is an organometallic cation where it might displace any catalytic magnesium ions or it may even interact with the negatively charged backbone of the RNA, such as aminoglycosides (Sucheck & Wong, 2000;Arya et al, 2001;Bryan et al, 2004;Bakkour et al, 2007).…”
Section: Environmental Toxicantsmentioning
confidence: 99%
See 1 more Smart Citation